Sino-African relations: some solutions and strategies to the policy syndromes - Simplice A. Asongu; John Ssozi (African Governance and Development Institute (AGDI), 2015)
We survey about 110 recently published studies on Sino-African relations; put some structure on the documented issues before suggesting some solutions and strategies to the identified policy syndromes. The documented issues classified into eight main strands include, China: targeting nations with abundant natural resources; focusing on countries with bad governance; not hiring local workers; outbidding other countries by flouting environmental and social standards; importing workers that do not integrate into domestic society and living in extremely simple conditions; exhibiting low linkages between her operations and local businesses; exporting low quality products to Africa; and the emergence of China hindering Africa's development.
Keywords: F19; F21; O10; O19; O55; 330; Economic relations; China; Africa